Very Long-Term International Housing Price Trends - Dasom Hong; Danny Dorling (Critical Housing Analysis)
Against the backdrop of recent global house price inflation, this paper addresses the question commonly asked about asset price booms and crises: ‘Is this time different?’ To identify the distinctive characteristics of today’s house price booms, we examined the long-term history of housing prices in five capital cities: Amsterdam, London, Beijing, Seoul, and Tokyo. Specifically, we employed house price, annual income, and average expenditure data to estimate real house price indices from the 1620s to the 2020s. The findings indicate that recent house price inflation is distinct not in severity but in synchronicity. The amplitude of house price booms and busts has remained consistent. However, house price cycles that historically moved independently have, in recent decades, more often shown similar variations both regionally and internationally. Now, prices tend to rise and fall together, but do not rise above the historical peaks of the past.